Applied Chemistry Training Based On Entrepreneurship For Chemistry Teachers Of Madrasah Aliyah (MA) In West Sumatera Province - Fauzana - Gazali (Fakultas MIPA Universitas Negeri Padang, 2020)
The aims of this community service are 1) to increase knowledge of Madrasah Aliyah’s (MA) chemistry teachers in West Sumatra about applied chemistry that can be practiced in entrepreneurship learning in MA, 2) to guide chemistry teachers in designing several applied chemistry experiments that can be done by MA’s students; 3) to practice some applied chemistry experiments that are suitable for MA’s students. The Implementation Methods are lecture, group discussions, and workshop on entrepreneurship, the packaging and marketing of applied products as well as experiment on several applied chemistry topics that are suitable for MA students. We hope that knowledge and skills obtained from this activity ease teachers in teaching entrepreneurship subjects to MA students more professionally as demanded by curriculum.